THE EFFECT OF WORK STRESS AND WORK ENVIRONMENT ON TEACHER PERFORMANCE AT SMPN 21 BEKASI CITY - Fadhli, Muhammad; Yaman, Bahrul (Journal of Finance, Economics and Business, 2024)
The research aims to see and analyze the influence of Job Stress and Work Environment on Teacher Performance. This research uses a quantitative approach with research subjects at SMPN 21 Bekasi City. The data used in this research is primary data consisting of interviews, questionnaires, observations and secondary data consisting of literature studies such as journals, books, decrees, government policies. In this research, the analytical method used is multiple regression analysis with a significance level of 5% with IBM SPSS V26 application software. A total of 33 statements were issued using Google Form with a total of 40 respondents determined using a non-probability sampling method through a saturated sample. The results of this research show that 1) Work stress has an effect on performance with the calculated T value obtained with a significance value of 0.000 which indicates that this value is smaller than 0.05 (0.000 < 0.05) and the calculated t value is 2.763 > t table 1.665. 2) the work environment influences performance with the Tcount value obtained with a significance value of 0.000 which indicates that the value is smaller than 0.05 (0.000 < 0.05) and the tcount value is 2.670 > ttable 1.665. 3) work stress and the work environment influence performance with a calculated F value of 6.718 > F table 3.119 and with a significance value of 0.003 which is smaller than the probability of 0.05 or a value of 0.003 < 0.05.